Manipulasi Temperatur Terhadap Perkembangan Sex Ratio Black Shoulder Fly (Hermetia illucens) - Trisno Haryanto; Nabila Putri Effendi; Trisnowati Budi Ambarningrum; Eko Setiyono; Hery Pratiknyo (Biotropic : The Journal of Tropical Biology, 2024)
Temperature is one of the factors that influences the life cycle of Hermetia illucens. This research aimed to determine the effect of temperature differences stimulated at the larval stage on the sex ratio of H. illucens. Knowledge of the correct use of temperature can be used as a reference in cultivating H. illucens. The research design used a Completely Randomized Design (CRD) with temperature variations (27oC; 30oC : 36oC). The variables observed included the sex ratio of H. illucens. Data were analyzed using one way ANOVA at a significance level of 95%. The research results show that the optimal sex ratio for cultivation is at room temperature (24°-31°C), namely 55% females and 45% males. The 27°C temperature treatment had the highest number of female, 70.83%, while the number of male was the highes. found at a temperature of 30°C, 62.50%.